Effect of Different Size of Broad Bed and Furrow on Runoff and Soil Loss and Productivity of Groundnut (Arachis hypogea L.) under Rainfed Conditions - Vekariya, P. D.; Sanepara, D. P.; Limbasia, B. B.; Sharma, G. R.; Akbari, K. N. (International Journal of Bio-resource and Stress Management, 2015)
A field experiment was initiated during rainy (kharif) season of 2003-04 to 2009-10 in medium black soil at Main Dry Farming Research Station, Targhadia (Rajkot), Gujarat, India to evaluate the different size of broad bed and furrow on the surface runoff and soil loss and productivity of groundnut which is the main crop of Saurashtra. The experiment was laid out in randomized block design with three replications having 4 treatments viz., flat bed (45 cm row spacing), broad bed (60 cm width) and furrow (30 cm) with 2 rows, broad bed (90 cm width) and furrow (45 cm) with 3 rows, broad bed (120 cm width) and furrow (60 cm) with 4 rows in runoff plot. Pooled results revealed significantly highest pod (932 kg ha-1) and haulm (3234 kg ha-1) yield under the broad bed (90 cm width) and furrow (45 cm) with 3 rows along with the minimum runoff (22.73%) and soil loss (483.40 kg ha-1). Higher mean soil moisture content (25.87% and 26.25%) was recorded under the both soil depths 0-15 cm and 15-30 cm, respectively under the broad bed (90 cm width) and furrow (45 cm) with 3 rows, while lowest (24.24% and 24.87%) were recorded in the flat bed control. The broad bed (90 cm width) and furrow (45 cm) with 3 rows also gave the highest net returns of ` 23662 ha-1 with the benefit: cost ratio of 2.69.